If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -12 = 11 + -2p Reorder the terms: -12 + 2p = 11 + -2p Solving -12 + 2p = 11 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. -12 + 2p + 2p = 11 + -2p + 2p Combine like terms: 2p + 2p = 4p -12 + 4p = 11 + -2p + 2p Combine like terms: -2p + 2p = 0 -12 + 4p = 11 + 0 -12 + 4p = 11 Add '12' to each side of the equation. -12 + 12 + 4p = 11 + 12 Combine like terms: -12 + 12 = 0 0 + 4p = 11 + 12 4p = 11 + 12 Combine like terms: 11 + 12 = 23 4p = 23 Divide each side by '4'. p = 5.75 Simplifying p = 5.75
| -[7x+[-4x+(-2+4x)]-(5x+1)]=0 | | -5n+9+7n=7n-8n-9 | | 8+13x=216 | | 1/5 | | 4x-17=2x+4 | | f(x)=8cosx | | -4y-9=6y+11 | | -2x^2-x=20 | | 11/2X=10 | | X^2+2x+4=3 | | 3(x+5)+2x=5x-15 | | 6x+7x+8=540 | | x^2-(m+1)*x+m=0 | | x^5-7x^3+9x=-x | | 6x+7x+8=360 | | x/187 | | (8,3)x= | | 3(10+x)=3 | | 6x+7x+8=36 | | x-41=-6 | | 12x-3-2x=0 | | 6/7a=16 | | 6x+3-9x=12-15x+12x-9 | | 4a^2+12a-27=0 | | (2/3)x=-9 | | 1/3d(60-t) | | -2(-7+3x)=-22 | | 3(2c-1)-2=2c+3 | | 6(10-3x)=10-8x | | m-20=10 | | 3/14N=3/16 | | (4t+5)(3t+10)=0 |